2007
DOI: 10.1007/bf03021708
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose sufentanil dœs not potentiate intra-thecal morphine for perioperative analgesia after major colorectal surgery

Abstract: Purpose: Both intrathecal sufentanil (ITS) and intrathecal morphine (ITM) improve analgesia in obstetrical or cardiac procedures. From a pharmacokinetic standpoint, combining these two opioids may improve perioperative analgesia. We performed a prospective randomized double-blind study to compare the analgesic efficacy of ITM alone vs a mixture of a low dose of ITS plus ITM for perioperative pain relief in colorectal surgery. Methods:Eighty adult patients undergoing colorectal surgery were randomly allocated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
2
0
1
Order By: Relevance
“…The fact that opioid analgesics have many unwanted side-effects such as nausea, vomiting, urinary retention, sedation, respiratory depression, drug dependence, dizziness and dry mouth (Higgins et al, 1994;Liukkonen et al, 2002;Akca et al, 2004;Horattas et al, 2004) tends to reduce their appeal further by complicating recovery and lengthening hospitalization (Higgins et al, 1994). Nevertheless, combinations of analgesics with different pharmacokinetic properties, either two opioids or an opioid with another class of analgesic agent, may increase analgesic effectiveness while reducing the worst of the side-effects (Culebras et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that opioid analgesics have many unwanted side-effects such as nausea, vomiting, urinary retention, sedation, respiratory depression, drug dependence, dizziness and dry mouth (Higgins et al, 1994;Liukkonen et al, 2002;Akca et al, 2004;Horattas et al, 2004) tends to reduce their appeal further by complicating recovery and lengthening hospitalization (Higgins et al, 1994). Nevertheless, combinations of analgesics with different pharmacokinetic properties, either two opioids or an opioid with another class of analgesic agent, may increase analgesic effectiveness while reducing the worst of the side-effects (Culebras et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Sufentanil was an important intraoperative adjuvant because it allowed the use of spinal anesthesia for cesarean section with small doses of local anesthetic (8 and 10 mg of bupivacaine). Culebras et al 24 found that low doses of sufentanil did not potentiate the effect of intrathecal morphine used for postoperative analgesia after colorectal surgery 24 .…”
Section: Discussionmentioning
confidence: 99%
“…O sufentanil foi importante adjuvante no intra-operatório, pois permitiu realização de raquianestesia para cesariana com doses pequenas de anestésico local (8 e 10 mg de bupivacaína). Culebras et al (2007) observaram que baixas doses de sufentanil não potencializaram o efeito da morfina intratecal, usado na analgesia pós-operatória, em cirurgia colo-retal (85) .…”
Section: Chanranchakul Et Al (2002) Não Observaram Diferenças Naunclassified